Characterization of beef cattle breeds by virtue of their performances in the National Beef Cattle Performance and Progeny Testing Scheme - Schoeman, S.J. (1996)
Average growth and body weight data, which comprised 745 400 weaning records and 14 990 Phase C growth records of young bulls of 16 breeds were obtained from the National Beef Cattle Performance and Progeny Testing Scheme and used in this re-analysis to characterize breeds for a variety of important traits. Phenotypically, mature breed size (X) was found to be significantly related to birth weight (y= 2.85 + 0.066X), weaning weight (y= 25.8 + 0.369X) and growth rate (y= 320 + 2.28X). Nevertheless, some breeds deviate considerably from their predicted values. Productive efficiency was, however, unrelated to mature breed size and dual-purpose breeds tended to be the most efficient. They were also the breeds showing the highest degree of sexual dimorphism.